2023
DOI: 10.1177/11297298231178064
|View full text |Cite
|
Sign up to set email alerts
|

Safe Insertion of Arterial Catheters (SIA): An ultrasound-guided protocol to minimize complications for arterial cannulation

Abstract: Direct puncture and cannulation of peripheral arteries is frequently performed in critical care and in emergency settings, mainly for hemodynamic monitoring and blood sampling. While there is abundant literature on peripheral arterial cannulation in children and adults, there is still scope for clinical improvements which may impact on patient safety. Although the radial artery is the most frequently utilized access site today, due to its superficial proximity, ease of access, and low risk of adverse events, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…These include visual assessment of skin and collateral circulation, pre-procedural ultrasound assessment taking into consideration diameter, sterile technique, administration of local anesthetics, correct insertion technique (ie, use of ultrasound, angle of insertion between 30 and 45°, "bevel-down" needle approach), assessment of catheter length (recommendation that >65% of the catheter length should be within the lumen of the vessel), proper catheter securement. 19 Due to the theoretical risk of cerebral air emboli, gentle flushing of the catheter when needed is advised to minimize the risk of air embolization. Furthermore, an individualized approach should always be employed, taking into consideration the indication for catheter placement, patient's hand dominance, risk of bleeding, and presence of peripheral vascular disease, among others.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include visual assessment of skin and collateral circulation, pre-procedural ultrasound assessment taking into consideration diameter, sterile technique, administration of local anesthetics, correct insertion technique (ie, use of ultrasound, angle of insertion between 30 and 45°, "bevel-down" needle approach), assessment of catheter length (recommendation that >65% of the catheter length should be within the lumen of the vessel), proper catheter securement. 19 Due to the theoretical risk of cerebral air emboli, gentle flushing of the catheter when needed is advised to minimize the risk of air embolization. Furthermore, an individualized approach should always be employed, taking into consideration the indication for catheter placement, patient's hand dominance, risk of bleeding, and presence of peripheral vascular disease, among others.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] Similarly, recent literature has reemerged on the role of the axillary artery for hemodynamic monitoring of critically ill patients, in addition to existing literature which dates back to the 1970's. [15][16][17][18][19][20] These recent studies have shown a high success rate of axillary arterial catheter placement when using ultrasound. Despite the recent publications of the above mentioned studies, literature on the safety profile of axillary arterial catheters remains limited.…”
Section: Introductionmentioning
confidence: 99%
“…It is, therefore, possible that nonattending anesthesiologists and palpation techniques were used for these failed attempts, but these details were not captured in our dataset. At our institution, ultrasound is used after failed attempts to ensure the target artery remains suitable and there is no appreciable vasospasm or hematoma [33,34].…”
Section: Discussionmentioning
confidence: 99%